Comparison of modified Minitek system with Staph-Ident system for species identification of coagulase-negative staphylococci. - Crouch, S F (J Clin Microbiol, 1987)
A modified Minitek system (BBL Microbiology Systems, Cockeysville, Md.) for species identification of coagulase-negative staphylococci was compared with the Staph-Ident system (Analytab Products, Plainview, N.Y.). The conventional method of Kloos and Schleifer (J. Clin. Microbiol. 1:82-88, 1975) was used as the reference method for identification. When tested with 78 coagulase-negative staphylococcal isolates from 63 children with cancer. Minitek concurred with the conventional identification in 67 (86%) isolates and Staph-Ident concurred in 61 (78%) isolates. Identification of species other than Staphylococcus epidermidis was better with Staph-Ident (19 of 23 isolates) than with Minitek (14 of 23 isolates). Concordance of results was likewise high, 88% (7 of 8) for Minitek and 100% (8 of 8) for Staph-Ident in studies with eight coagulase-negative staphylococcal strains obtained from the American Type Culture Collection (Rockville, Md.). We conclude that the modified Minitek system is a practical and reliable test for identifying coagulase-negative staphylococci in clinical microbiology laboratories. Its versatility and larger repertoire of biochemical tests may offer advantages over the Staph-Ident system.